Osteochondritis Dissecans: Etiology, Pathology, and Imaging with a Special Focus on the Knee Joint. (October 2018) - Bruns, Juergen; Werner, Mathias; Habermann, Christian
This article is a review of the current understanding of the etiology, pathogenesis, and how to diagnose and treat knee osteochondritis dissecans (OCD) followed by an analysis of and outcomes of the treatments available. OCD is seen in children and adolescents with open growth plates (juvenile OCD) and adults with closed growth plates (adult OCD). The etiology of OCD lesions remains unclear and is characterized by an aseptic necrosis in the subchondral bone area. Mechanical factors seem to play an important role. Clinical symptoms are unspecific. Thus, imaging techniques are most important. Regarding treatment, a tremendous number of publications exist. Spontaneous healing is expected unless there is an unstable fragment, and treatment involves rest and different degrees of immobilization until healing. Patients with open physes and low-grade lesions have good results with conservative therapy. When surgery is necessary, the procedure depends on the stage and on the state of the cartilage. With intact cartilage, retrograde procedures are favorable. When the cartilage is damaged, several techniques can be used. While techniques such as drilling and microfracturing produce reparative cartilage, other techniques reconstruct the defect with additional osteochondral grafts or cell-based procedures such as chondrocyte transplantation. There is a tendency toward better results when using procedures that reconstruct the bone and the cartilage and there is also a trend toward better long-term results when comorbidities are treated. Severe grades of osteoarthrosis are rare.